Dieta e sobreposição de nicho de aves insetívoras de sub-bosque no sudeste do Brasil - Lima, Ana Luísa de Carvalho (2017)
The diet and feeding niche relationships of understorey insectivorous birds was investigated in different microhabitats, based on their diet (faecal samples), morphology (body mass and beak length), and availability of resources in a forest remnant in Southeastern Brazil. The niche overlap survey were made in three different groups, according to the exploration of microhabitats, foliage insectivores (IF), ground insectivores (IC) and trunk insectivores (IT). The fecal number samples was ≥ 10. The niche relationships studies of foliage-gleaning insectivores birds included four species, Basileuterus culicivorus, Dysithamnus mentalis, Hemitriccus diops and Platyrinchus mystaceus (Chapter I). For trunk insectivores, two woodcreeper species, Sittasomus griseicapillus and Xiphorhynchus fuscus (Chapter II) and for ground insectivores, Conopophaga lineata, Myiothlypis leucoblephara and Pyriglena leucoptera (Chapter IV). The feeding preference of M. leucoblephara was also investigated for taxa and prey sizes (Chapter III). The study was carried between 2013 and 2016 in a semideciduous seasonal forest fragment at Bom Jardim Farm, in the municipality of São Vicente de Minas, Southern Minas Gerais. Five sample lines were established and the birds were captured with ornithological networks (10 in each line). The invertebrates was collected on the ground (litter) and in the foliage (branch-clipping), both along the sample lines. Were carried out 3000 h / r, totaling 714 catches of 586 component individuals of 48 species, of which 27 were insectivorous species. The diet composition, by taxa, was not enough to define niche segregation patterns in the groups investigated. There was high niche overlap and no differentiation of niche amplitudes among species at each microhabitat. The differential prey consumption with respect to size is pointed here as one of the factors responsible for mediating the coexistence of species among the IF. However, same pattern was not observed among IT, whose morphological differences did not influence the invertebrates size consumed. On the other hand, CIs presented a positive relationship between body mass and prey size data, where larger birds also consumed the largest invertebrates. Although the results indicated food niche segregation in relation to prey size between M. leucoblephara and the other two species of CI, there was no niche segregation between C. lineata and P. leucoptera, morphologically close species. According to the results, the diet composition, by taxa, was not enough to define niche segregation patterns among the insectivorous birds surveyed here. Instead of, differential consumption of prey size seems explain better the results. Nevertheless, the present survey suggests that information obtained here together to the birds behavioral data, especially those conserned to differential exploration in space-time, can provide a better understanding of the relationships of trophic niche established between these species at each microhabitat.